2023
DOI: 10.1021/prechem.3c00023
|View full text |Cite
|
Sign up to set email alerts
|

In Situ High-Temperature Reaction-Induced Local Structural Dynamic Evolution of Single-Atom Pt on Oxide Support

Abstract: The dynamic evolution of active site coordination structure during a high-temperature reaction is critically significant but often difficult for the research of efficient single-atom catalysts (SACs). Herein, we for the first time report the in situ activation behaviors of the local coordination structure of Pt single atoms (Pt 1 ) during the high-temperature oxidation of light alkanes. The distinctly enhanced activity of the catalyst is attributed to the in situ evolved Pt 1 −oxygen vacancy (Pt 1 −OV) combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The single-atom catalyst (SAC), a new concept first proposed by Zhang, Li, and Liu et al, is regarded as one of the landmark studies in heterogeneous catalysis. In the past decade, a series of new concepts related to SACs have been derived based on the static and dynamic active center of the reaction and the atomic type of the active center, such as dynamic single-atom catalysts (DSACs), , single-cluster catalysts (SCCs), which include the so-called dual-atom-site catalysts (DASCs), single-atom alloy (SAA), and nanosingle-atom-site catalysts (NSASCs). Currently, SACs have been widely used in diverse photocatalytic, electrocatalytic, and thermal catalytic reactions such as CO oxidation, H 2 production, CO 2 reduction, N 2 fixation, NO oxidation, WGS reaction, and so on, owing to their excellent catalytic activity and selectivity, clear-cut coordination environment of active centers, and the maximum atomic utilization of metals. Especially, Lin et al reported a new SAC Ir 1 /FeO x , which shows higher catalytic activity than its cluster or nanoparticle counterpart, and even than the most active Au- or Pt-based catalysts for WGS reaction. Combined with experimental results, Liang et al systematically studied the catalytic mechanism of the WGS reaction using first-principles calculations, and proposed a new dual metal active site synergistic redox mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The single-atom catalyst (SAC), a new concept first proposed by Zhang, Li, and Liu et al, is regarded as one of the landmark studies in heterogeneous catalysis. In the past decade, a series of new concepts related to SACs have been derived based on the static and dynamic active center of the reaction and the atomic type of the active center, such as dynamic single-atom catalysts (DSACs), , single-cluster catalysts (SCCs), which include the so-called dual-atom-site catalysts (DASCs), single-atom alloy (SAA), and nanosingle-atom-site catalysts (NSASCs). Currently, SACs have been widely used in diverse photocatalytic, electrocatalytic, and thermal catalytic reactions such as CO oxidation, H 2 production, CO 2 reduction, N 2 fixation, NO oxidation, WGS reaction, and so on, owing to their excellent catalytic activity and selectivity, clear-cut coordination environment of active centers, and the maximum atomic utilization of metals. Especially, Lin et al reported a new SAC Ir 1 /FeO x , which shows higher catalytic activity than its cluster or nanoparticle counterpart, and even than the most active Au- or Pt-based catalysts for WGS reaction. Combined with experimental results, Liang et al systematically studied the catalytic mechanism of the WGS reaction using first-principles calculations, and proposed a new dual metal active site synergistic redox mechanism.…”
Section: Introductionmentioning
confidence: 99%